An Empirical Investigation of the Impact of Dividend Announcement on the Selected Stock Prices traded on NSE. - Dr. Rajesh Kumar (International Journal of Advanced Science and Technology, 2020)
Observing the price movement of shares is a research area that caught the interest of various researchers, academicians and organizations. Over the last four decades, behavior of share prices has been the center of attraction to such investigation more than any other topic of finance. Our study attempts to make the understanding of topic easy, which is impact of dividend announcement on share prices. Our study focused on share price fluctuation of 15 Automobiles companies listed on NSE, India due to dividend announcement. Methodology used to examine the Impact are normal return, abnormal return, Mean CAR and t-test and as result, out of 15 sample companies 66.67% company’s shares prices has been decreased in post -announcement period which were positive in pre-announcement period. However, the 66.67% is not properly appropriate to come to any final decision regarding the impact of dividend announcement of the corresponding share prices of the concerned firms.